Towards a Model for Analyzing the Impact of Macroeconomic Adjustment Policies on Households: A Review - Aniceto Jr. C. Orbeta (Philippine Institute for Development Studies (PIDS), 1994)
This paper has two objectives: determination and assessment how the existing empirical household models capture the effects of changes in macroeconomic variables on the welfare of the Filipino household and identification of research gaps in the literature. For some of the Philippine models to better capture the effects of macroeconomic adjustments, this paper suggests ways of model modification.
Keywords: 330; health sector; computable general equilibrium (CGE); MIMAP; adjustment policies; intertemporal decisions; health and nutrition; education; intrahousehold allocation